Analyzing Economic Determinants of Consumer Preferences in The Digital Market Using The Theory of Consumer Behavior - Kalaivani , Dr.M.; Murugan, Dr.P. Sundara Bala; Selvaraj , Dr. Vijayakanthan; Anitha , Dr.L. (International Journal of Accounting and Economics Studies, 2025)
In the ever-increasing technological change, understanding the economic determinants that shape consumer behavior is vital for any business trying to compete in the digital marketplace. This research analyzes the economic factors that shape consumer choices in digital markets through the lens of the Theory of Consumer Behavior. It examines how traditional economic aspects like pricing mechanisms, income levels, consumer self-satisfaction, substitution effects, and digital price transparency interact with convenience, immediacy, and algorithmic advertising to influence consumer spending. The study utilizes the Theory of Consumer Behavior to maximize satisfaction given an income and a set of choices while adjusting the classical constituents to fit the digital marketplace. It incorporates the definition of marginal utility, opportunity cost, and budget constraints. It analyzes their relevance and change in the online market characterized by lower information asymmetry and instantaneous price comparison. The study uses quantitative methodology and a survey technique. Data was obtained from 500 consumers with diverse backgrounds and geographical locations. Employing multiple regression analysis and constructing structural equation models, the study surfaces key digital market preferences and consumer behavior predictors. As anticipated, the study results confirm the widely held belief of the overriding importance of price. However, it was observed that value perception and ease of purchase are significant contributors to the modern economic environment. Furthermore, the analysis suggests that income elasticity acts as a moderating factor whereby consumers with higher income display a divergence in preference patterns from those with lower income.